Cour years of the RVSP (Revista Venezolana de Salud Pública, 2018)
The Venezuelan Public Health Magazine (RVSP) is now four years old, with eight numbers to its credit, accumulating a total of 67 articles, for an average of 8 per number; it has been a hard but comforting work, which is appreciated when seeing its fruits, where only, to mention to the technological platform of the UCLA (http://bibvirtual.ucla.edu.ve/RVSP/), they are presented more than 133,000 entries or queries, where the most widely read article has been the contamination of cabbage enteroparasitaria, with 45,000 entries, or to mention another platform such as ISSUU, where only the second number has 1937 readings, plus 28,178 impressions, according to the origin of the consultant, in order of frequency, appear Venezuela, Mexico, Spain, Peru, Ecuador, Argentina, Guatemala and the Dominican Republic, or in the case of IMBIOMED (Mexican Index of Latin American Biomedical Journals), with more than 6000 entries, auditable. All this is very pleasing because the visibility of the journal is increasing every day, which allows thousands of users who rely on RVSP to be a safe source of knowledge in Public Health.
Keywords: Venezuela; Journal; Public; Heald; NaWarao